Metabolomic profiles in individuals with negative affectivity and social inhibition: A population-based study of Type D personality - Altmaier, Elisabeth; Emeny, Rebecca T.; Krumsiek, Jan; Lacruz, Maria E.; Lukaschek, Karoline; Haefner, Sibylle; Kastenmueller, Gabi; Roemisch-Margl, Werner; Prehn, Cornelia; Mohney, Robert P.; Evans, Anne M.; Milburn, Michael V.; et al. (Psychoneuroendocrinology, 2013)
Background: Individuals with negative affectivity who are inhibited in social situations are characterized as distressed, or Type D, and have an increased risk of cardiovascular disease (CVD). The underlying biomechanisms that link this psychological affect to a pathological state are not well understood. This study applied a metabolomic approach to explore biochemical pathways that may contribute to the Type D personality. Methods: Type D personality was determined by the Type D Scale-14. Small molecule biochemicals were measured using two complementary mass-spectrometry based metabolomics platforms. Metabolic profiles of Type D and non-Type D participants within a population-based study in Southern Germany were compared in cross-sectional regression analyses. The PHQ-9 and GAD-7 instruments were also used to assess symptoms of depression and anxiety, respectively, within this metabolomic study. Results: 668 metabolites were identified in the serum of 1502 participants (age 32-77); 386 of these individuals were classified as Type D. While demographic and biomedical characteristics were equally distributed between the groups, a higher level of depression and anxiety was observed in Type D individuals. Significantly lower levels of the tryptophan metabolite kynurenine were associated with Type D (p-value corrected for multiple testing. = 0.042), while no significant associations could be found for depression and anxiety. A Gaussian graphical model analysis enabled the identification of four potentially interesting metabolite networks that are enriched in metabolites (androsterone sulfate, tyrosine, indoxyl sulfate or caffeine) that associate nominally with Type D personality. Conclusions: This study identified novel biochemical pathways associated with Type D personality and demonstrates that the application of metabolomic approaches in population studies can reveal mechanisms that may contribute to psychological health and disease. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Kynurenine; Metabolomics; Negative affectivity; Population study; Social inhibition; Type D personality